Investigation of an electrostatic discharge protective biodegradable packaging foam in the logistic chain - Mojzes, Ákos (Logistics and sustainable transport, 2014)
Since the beginning of the 20th century, logistics has undergone a huge technological development, which has, however, resulted in many negative effects as well. The industry, particularly in the packaging industry has been a massive waste producer, although recently it has forced the use of new materials and it started to focus on environmentally friendly technologies. During the transportation of finished and semi-finished Electrostatic Discharge (ESD) sensitive products, the product packaging system has a vital role. These kind of packaging materials must be suitable to both logistic (protection against mechanical and environmental stresses) and special ESD protection requirements. During the transportation of printed-circuit electronic products, ESD defense is then of primary significance. However there is a huge disadvantage for the use of various shield bags. Namely, this kind of associated packaging is particularly pollutant, it causes a lot of inconvenience in the form of waste. In order to rule out these materials from the packaging system, new innovative solutions have to be found. The investigated TPS (thermoplastic starch biodegradable foam) is subjected to a validation, a long process to certify that this material unites properties of two types of packaging materials at the same time. On the one hand, this packaging foam has to meet the requirements product defense. On the other hand, the material must be anti-static under the logistic stress effects. In case it is found suitable, it can be an alternative of the conventional materials. In this article, we investigate the ESD characteristic of TPS foam. As this material sensitive for environmental parameters during transportation, we make the relevant Surface Resistance (Rs) tests on different temperature and humidity conditions. Based on result, the decision of the application can be done, as an ESD packaging material.
Keywords: biodegradable; biološko razgradljivo; eco-friendly; embalaža; ESD protection; okolju prijazno; TPS foam